SIMULTANEOUS DETERMINATION METHOD OF BHA, BHT, PROPYL GALLATE, AND TBHQ IN MARGARINE USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Christinawaty; Damayanti, Sophi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Antioxidants are food additives in oil and fat products usually to decrease the process of rancidity by preventing the oxidation such as in margarine. BHA, BHT, propyl gallate, and TBHQ are commonly used antioxidants. Combinations of antioxidants are generally used in the food product. Therefore, analytical method which is capable to measure the antioxidants simultaneously, is required. This study was aimed to obtain analytical method for determination of BHA, BHT, propyl gallate, and TBHQ using HPLC in margarine. The analysis was using Waters column Xbridge C18 (4.6 x 150 mm, 5μm) and 280 nm ultraviolet detector. The mobile phase was a mixture of 1% acetic acid in acetonitrile and 1% acetic acid (3:7). The flow rate was set at 1.7 ml/min. The calibration curve of BHA, BHT, propyl gallate and TBHQ were linear with correlation coefficient r = 0.9999, 0.9996, 0.9998 and 0.9998, respectively. Limit of detection and limit of quantitation of BHA, BHT, propyl gallate and TBHQ were 2.6217 and 7.9445 µg/ml; 4.1837 and 12.6777 µg/ml; 2.494 and 7.559 µ/ml; 2.1272 and 6.4461 µg/ml, respectively. Inter day precision of the method was expressed as RSD with result; BHA, BHT, propyl gallate, and TBHQ were 0.1553; 0.4576; 0.0237; 4.8106 %; respectively whereas recovery using standard addition method were 105.38; 107.87; 86.50; 83.64 % respectively. Based on the obtained results, it can be concluded that this method has been successfully developed and validated for the determination of antioxidants BHA, BHT, propyl gallate, and TBHQ in margarine.